OIL AND GAS INDUSTRY IN UZBEKISTAN - Kochkarov Ulug‘bek Kabuljanovich (Galaxy International Interdisciplinary Research Journal, 2021)
In this article is given information about the oil industry, gas industry, our country has become a major exporter of gas, polyethylene and refined petroleum products, oil and gas business is one of the most lucrative and labor-intensive industries of our time, it is processed to extract the necessary substances in the oil, the first step in the extraction of oil is the separation of colorless substances - gasoline and gasoline fractions, and the product of each fraction.